2000
DOI: 10.1051/lait:2000121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mare caseins. Identification of $\alpha_{{\bf S1}}$- and $\alpha_{{\bf S2}}$- caseins

Abstract: -Whole mare (Mongolian and French breeds) casein was obtained from skim milk by isoelectric precipitation (pH 4.6) at 22 °C. In another series of experiments, equine caseins were fractionated after isoelectric precipitation at 4 °C, according to their sensitivity to temperature, on one hand, the pH of the resulting pellet was adjusted to 6.5 before centrifugation (45 000 g for 30 min) at 4 °C; on the resulting casein fraction which precipitated was named the cold precipitated (CP) fraction. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…Another factor may be that equine milk contains β-caseins with variable degree of phosphorylation. The less phosphorylated forms of β-caseins can act on the surface of the casein micelles and thereby play the role of the κ-casein [25]. Even though a certain amount of the human casein was degraded in the gastric juice, the degradation pattern was very different from the profile observed for the equine caseins.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another factor may be that equine milk contains β-caseins with variable degree of phosphorylation. The less phosphorylated forms of β-caseins can act on the surface of the casein micelles and thereby play the role of the κ-casein [25]. Even though a certain amount of the human casein was degraded in the gastric juice, the degradation pattern was very different from the profile observed for the equine caseins.…”
Section: Discussionmentioning
confidence: 92%
“…Human milk contains 1.0 g·L −1 κ-casein [24]. It has been suggested that the high content of β-caseins and the variable degree of phosphorylation of equine milk compensate for the low content of κ-casein in the micelle formation [25].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the heterogeneity shown in the whole casein analysis by 2-DE may be due to a variable degree of phosphorylation and to genetic variants of αs1-and β-caseins [32][33][34].…”
Section: Characterization Of Donkey Milk Protein Fraction By Twodimenmentioning
confidence: 91%
“…Separation of the protein fraction into caseins and whey proteins was conducted according to a modified method from Ochirkhuyag et al (2000). Specifically, whole casein was obtained from skimmed milk by isoelectric precipitation (pH 4.3) at 22°C using 1N HCl.…”
Section: Materials and Methods Preparation Of Milk Samplesmentioning
confidence: 99%